2016
DOI: 10.1136/openhrt-2016-000441
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of warfarin in dialysis patients with atrial fibrillation: a systematic review and meta-analysis

Abstract: ObjectiveTo systematically review and meta-analyse the risk–benefit ratio of warfarin users compared with non-warfarin users in patients with atrial fibrillation (AF), who are undergoing dialysis.MethodsWe searched PubMed/MEDLINE, EMBASE, SCOPUS, Web of Science, Cochrane Library, grey literature, conference proceedings, trial registrations and also did handsearch. Cohort studies without language restrictions were included. Two investigators independently conducted a full abstraction of data, risk of bias and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 70 publications
4
35
0
5
Order By: Relevance
“…Of the 20 studies reviewed, 14 demonstrated lack of benefit or even harm. The strongest evidence comes from large retrospective studies and multiple meta‐analyses …”
Section: Management By Ckd Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Of the 20 studies reviewed, 14 demonstrated lack of benefit or even harm. The strongest evidence comes from large retrospective studies and multiple meta‐analyses …”
Section: Management By Ckd Stagementioning
confidence: 99%
“…Three large meta‐analyses, each including 13 to 20 studies and 37 000 to over 50 000 patients, failed to show benefit to the use of warfarin among ESRD or dialysis patients in either thromboembolism prevention or mortality reduction . They did, however, demonstrate increased risk of either all‐cause bleeding by 21% or major bleeding by 30% to 35% .…”
Section: Management By Ckd Stagementioning
confidence: 99%
“…Observational data support its use in CKD IV, [27][28][29][30] but the majority of studies of warfarin in ESRD, including large retrospective studies 31,32 and multiple meta-analyses, 30,33,34 demonstrate lack of benefit and possible harm. Further study with patient-level data is needed to evaluate the use of DOACs in patients with advanced CKD.…”
Section: Introductionmentioning
confidence: 99%
“…58,59 Inhibition of FXI may also attenuate clotting on the hemodialysis circuit, thereby further lowering the risk of bleeding associated with heparin therapy. In support of this concept, a small pilot study in hemodialysis patients revealed less clotting in the air trap and on the dialysis membrane with IONIS-416858 at doses of 200 or 300 mg than with placebo even though all patients received heparin during dialysis.…”
Section: Potential Indications For Fxi-directed Therapiesmentioning
confidence: 99%